Municipal driven fiber access network rollout - Jan Van Ooteghem; Koen Casier; Sofie Verbrugge; Didier Colle; Mario Pickavet; Luc De Heyn; Raf Meersman; Bart Rosseau (International Telecommunications Society (ITS), 2012)
A citywide fiber to the home network would certainly bring about a lot of advantages for the municipality. Still the operators tend to hold off, partly because of the very high deployment costs and often also because there is a medium high bandwidth network available. This is also the case for the city of Ghent in which an FTTH network is not available and does not seem to be planned in the near future. In this paper we investigate to which degree the municipality can play a role in triggering the rollout of FTTH or less extensive a fiber to the business rollout by initiating the first steps in the deployment. If a city plans to connect its own public buildings first, such as governmental offices and city services and in extension hospitals, schools, museums and other public care or recreational centers, it could already open up some of the advantages of an FTTH network to its citizens. One step further, the city could take a more foresighted deployment scenario into account, in which more ducts and feeders are deployed and some detours are allowed, to enable a faster and cheaper rollout towards businesses and/or residential customers. In this paper we investigate three rollout scenarios with varying focus and amount of foresight: sequential (noncoupled) rollouts; optimized for municipal, public and business areas; fully optimized network for all buildings in the city. The final scenario targets thus a future proof network topology for the whole city. The results of this study shows a much lower final cost when considering a full optimal rollout plan from the start for all buildings in your city. The potential value will also be higher, as the cost for furthermore rolling out towards a business and full FTTH network for inhabitants will be much lower. In addition a geomarketing methodology should be used selecting the most optimal areas focusing first on connecting municipal and other public buildings.
Keywords: 330; Techno-economics; network dimensioning; municipal network; geomarketing